The symptoms of and consequences to selection errors in recruitment decisions - M. Sutherland; A. Wöcke (South African Journal of Business Management, 2011)
The ability to select effective human capital has long been viewed as the bedrock of the human resource function and a driver of organisational success. There is a plethora of literature available on recruitment and selection methodologies but little empirical evidence of the consequences to selection errors. Data was gathered on 393 incidents of selection errors across a wide range of industries. The symptoms and attribution of, and the wide-ranging consequences to, these selection errors were documented. Methods to rectify the selection error and the outcome of those attempts were also explored. Recommendations based on these empirical findings are offered.
Keywords: 650